1990
DOI: 10.1364/ao.29.001249
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photorefractive beam fanning due to internal and external electric fields

Abstract: Significant increases (x10) in both speed and gain of the beam fanning process were obtained via three different methods in SBN and BSKNN. These methods involve the creation of a dc electric field either (1) externally, (2) by the pyroelectric effect, or (3) by thermally cycling the crystal and the presence of laser radiation. The enhanced effects were observed for both ordinary and extraordinary polarized light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…This led us to the question if pyroelectrically induced PRD can be observed in MgO:LN, even though it is known to show no conventional bulk-photovoltaic PRD, by choosing a suitable light intensity and creating a pyroelectric field [9][10][11][12]. Another open question was why damage was not observed in CLN under similar conditions.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…This led us to the question if pyroelectrically induced PRD can be observed in MgO:LN, even though it is known to show no conventional bulk-photovoltaic PRD, by choosing a suitable light intensity and creating a pyroelectric field [9][10][11][12]. Another open question was why damage was not observed in CLN under similar conditions.…”
Section: Motivationmentioning
confidence: 99%
“…(4) first, but as soon as the crystal is illuminated with, e.g., a Gaussian beam at a visible wavelength with E 0 being present, the photoconductivity in the center of the beam becomes larger than in the outer wings of the beam or the dark parts of the crystal. Thus, the increased photoconductivity together with E 0 causes a drift current that leads to screening of E 0 in the center of the beam [9,19]. According to Eq.…”
Section: B Prd Due To An Externally Applied Electric Field Ementioning
confidence: 99%
“…2 can be explained with Eqs. (5), (6), and (8). The measured value H of different samples is generally in the range of several tens of seconds, and the value of M depends on intensity.…”
Section: Dependence On Light Intensitymentioning
confidence: 99%
“…In 1990 the observation of enhanced photorefractive beam fanning because of the pyroelectric effect was reported. 6 Later the transient enhancement of amplification during two-wave mixing in Cu-doped KN SBN crystal was mentioned and attributed to pyroelectric fields, 7 but no detailed experimental results and analyses were given. More recently Korneev et al 8 observed an enhanced photorefractive grating by heating or cooling and by homogeneous illumination of a strontium barium niobate crystal with a cw laser.…”
Section: Introductionmentioning
confidence: 99%
“…This two-beam coupling forms the underlying process for both signal beam amplification in two-wave mixing and beam fanning [8][9][10][11] . In the case of signal beam amplification by two-beam coupling using a photorefractive material such as BaTiO 3 , there is considerable depletion of pump energy into the amplified signal and beam fanning because of the very large twobeam coupling efficiency .…”
Section: Introductionmentioning
confidence: 99%